2007
DOI: 10.1016/j.stem.2007.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Hematopoietic Precursor Division in Real Time

Abstract: Stem cells are thought to balance self-renewal and differentiation through asymmetric and symmetric divisions, but whether such divisions occur during hematopoietic development remains unknown. Using a Notch reporter mouse, in which GFP acts as a sensor for differentiation, we image hematopoietic precursors and show that they undergo both symmetric and asymmetric divisions. In addition we show that the balance between these divisions is not hardwired but responsive to extrinsic and intrinsic cues. Precursors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
273
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(287 citation statements)
references
References 42 publications
9
273
0
5
Order By: Relevance
“…Because the single plated cell might not represent the most primitive HSC, this value specifies the minimum number of cell divisions hematopoietic progenitors can undergo. The balance between asymmetric and symmetric HSC divisions has been estimated with Notch reporter mice to be Ϸ0.5 to 3.0; this value depends on the microenvironmental conditions of HSCs (46). Unfortunately no data are available to provide estimates for the magnitudes of the death rate and the number of additional cell divisions a JAK2V617F-positive progenitor can undergo; however, we can test the model for robustness with regard to these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Because the single plated cell might not represent the most primitive HSC, this value specifies the minimum number of cell divisions hematopoietic progenitors can undergo. The balance between asymmetric and symmetric HSC divisions has been estimated with Notch reporter mice to be Ϸ0.5 to 3.0; this value depends on the microenvironmental conditions of HSCs (46). Unfortunately no data are available to provide estimates for the magnitudes of the death rate and the number of additional cell divisions a JAK2V617F-positive progenitor can undergo; however, we can test the model for robustness with regard to these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Maillard and colleagues confirmed these findings using a conditional Rbpj knock-out mouse in which this DNA-binding factor required for Notch signaling also failed to demonstrate a role for Notch signaling in HSC development or function in adult animals [Maillard et al, 2008]. Although the relevance to physiologic Notch signaling in HSC has been called into question, the Notch pathway reporter mouse appears to be useful for studying the effects of specific oncogenes on symmetric cell division [Wu et al, 2007].…”
Section: Pathways Involved In Self-renewalmentioning
confidence: 92%
“…Later studies showed that there are two paralogous Msi genes in mammals (Msi1 and Msi2), and that the Msi1 gene expression marks tissue stem cells in brain, eye, and intestine [53]. Msi1 binds to and inhibits the translation of the mRNA for Numb, which specifies a differentiated cell fate in neural progenitors and HSCs [54,55]. The functional importance of Msi1 in neural stem cells, however, remains elusive.…”
Section: Let-7mentioning
confidence: 99%